2003
DOI: 10.1097/00042737-200312000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Affective disorders and quality of life in adult coeliac disease patients on a gluten-free diet

Abstract: In coeliac disease, affective disorders should be ascribed to difficulties in adjusting to the chronic nature of the disease rather than directly to the disease itself, thus giving an indication for preventive liaison psychiatric interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 23 publications
12
128
2
2
Order By: Relevance
“…Studies have not shown any relationship between the depression complaints observed in CD patients and age, gender, and socio-economic variables (19). According to the literature, there is no relationship between physical symptoms, such as abdominal pain and diarrhea, and depression symptoms (3,21,22). The control group in this study was similar to the study group in terms of age and gender.…”
Section: Esenyel Et Al the Mental Health Of Coeliac Childrenmentioning
confidence: 44%
“…Studies have not shown any relationship between the depression complaints observed in CD patients and age, gender, and socio-economic variables (19). According to the literature, there is no relationship between physical symptoms, such as abdominal pain and diarrhea, and depression symptoms (3,21,22). The control group in this study was similar to the study group in terms of age and gender.…”
Section: Esenyel Et Al the Mental Health Of Coeliac Childrenmentioning
confidence: 44%
“…The few studies that address this issue have measured adherence through self-report and/or questionnaires [16,26,31]. However, the questionnaires have not been validated, and self-reporting has been shown to be inaccurate [32]. Conversely, trained nutritionist evaluation shows a high correlation with intestinal biopsy abnormalities [17].…”
Section: Discussionmentioning
confidence: 99%
“…While these factors are important for QOL, one area that has received less attention is psychological symptoms and coping, despite higher rates of psychological symptoms within CD patients compared to the general population (16,(31)(32)(33)(34)(35)(36). Two studies found that increased depression and anxiety in CD were correlated with reduced QOL (16,36), while a recent study found that emotion-oriented coping was negatively related to QOL (37). In the broader context, the link between QOL, psychopathology, and coping is well established (38)(39)(40)(41)(42), with depression representing the greatest threat to QOL across a range of populations (38).…”
Section: )mentioning
confidence: 99%